Збереження історико-архітектурного середовища однієї з найдавніших вулиць Києво-Подолу – Боричів Тік - Горькова, А.О.; Котовська, М.Б.; Гоменюк, В.М. (Сіверщина в історії України, 2023)
Стаття присвячена дослідженню культурної спадщини м. Києва, зокрема висвітленню історії вулиці Боричів Тік та об’єктів культурної спадщини, які розташовані на ній. Визначено основні проблеми та перспективи для подальшого дослідження і збереження пам’яток, традиційного характеру історичного середовища вулиці шляхом застосування методу ревалоризації та музеєфікації окремих будівель і споруд, що мають архітектурну та історичну цінність та є знаковими для Києво-Подолу. The article is devoted to the study of cultural heritage of Kyiv, in particular to highlight the history of Borychiv Tik street and the objects of cultural heritage located on it. The basis of the research were archival documents and materials of the State Archives of Kyiv, as well as soviet and contemporary historiography devoted to urban planning and architecture of Kyiv between the middle and end of the 19th century. Based on little-known sources, the town planning history of Podil street of Borychiv Tik is briefly disclosed that partly retaining its ancient configuration and combining the architecture of different centuries: one- and two-story mansion-type houses built in the mid of 19th century – at the beginning of XX century, as well as modern administrative buildings and private town houses. The historical development of the street is formed by 12 monuments of architecture, urban planning and history, which are included in the State Register of Immovable Monuments of Ukraine. The main problems and prospects for further research and preservation of monuments, the traditional character of the historical environment of the street have been determined, by applying the method of revaluation and museification of buildings, which have architectural and historical value and are iconic for Kyiv-Podil.